IMPLEMENTASI CYBER PUBLIC RELATIONS DALAM MENINGKATKAN CITRA POSITIF PERUSAHAAN PT PLN (PERSERO) AREA KABUPATEN BONE - Zyani, Asrul; Jaya, Fahril; Mustadir, Mustadir (GROWTH Jurnal Ilmiah Ekonomi Pembangunan, 2024)
In today's modern era, the use of online electronic media is very much needed by every agency/company in its activities. PT PLN (Persero) Bone Regency Area is a State-Owned Enterprise (BUMN) of the PLN Parent Unit for the Bone Regency Area with the task of providing electricity for the public interest. Cyber Public Reactions, which are implemented using internet electronic media, aim to build brands and maintain trust and public understanding in order to create a positive image of the company through interactive two-way communications. Aims to determine the implementation of Cyber Public Relations in improving the positive image of the company PT PLN (Persero) Bone Regency Area. To achieve this goal, this research uses a type of qualitative descriptive research (describing or depicting) about the condition of objects systematically and accurately based on facts, data and information collected in the field in detail regarding the implementation and obstacles of PT PLN (Persero) Cyber Public Relations. ) Bone Regency area in using online communication media. The data collected is then processed to produce systematic and accurate data. The results of this research show several implementations of Cyber Public Relations in improving the positive image of the company PT PLN (Persero) Bone Regency Area, including; Optimizing the use of mainstream media, creating interactive communication between agencies and the public, forming a positive image by providing clarification and up to date information. Some of the obstacles faced in the implementation of Cyber Public Relations of PT PLN (Persero) in the Bone Regency area lie in the lack of Human Resources (HR) in managing the website, lack of coordination and technical problems.